Integrated management of bacterial wilt of tomato caused by Ralstonia solanacearum - SHARMA, J P; KUMAR, S; SINGH, DINESH (The Indian Journal of Agricultural Sciences, 2016)
An integrated management of bacterial wilt of tomato against race 1 biovar III of Ralstonia solanacearum was conducted with eleven treatment combinations on resistant (cv Swarna Lalima) and susceptible (cv. Pusa Ruby) of tomato from 2006 to 2009-10 during rainy seasons. The pooled analysis of different treatments × variety × date of sampling were showed significanteffects on Ralstonia population, wilt incidence and yield of the crop. This treatment also reduced R. solanacearum population and increased the yield 47.2% in cv. Swarna Lalima (343.7 q/ha) with B: C ratio (1.49:1) over resistant check.